Analysis of COD (Chemical Oxygen Demand) on Liquid Waste of Cheese Production in PT. XYZ, Yogyakarta with Iodometric Titration Method - Aini, Nurjannah; Juwitaningtyas, Titisari (Journal of Agri-Food Science and Technology, 2021)
PT. XYZ is one of food industry engaged in milk processing, organic cheese and creamer in Yogyakarta. Cheese production produces a large volume of liquid waste that it is used as natural fertilizer. Liquid waste of PT XYZ was not handled properly and pollute the environment. This research evaluates liquid waste using COD analysis. This study aims to determine the COD (Chemical Oxygen Demand) value of liquid waste produced by PT. XYZ and compared these results with the quality standards of liquid waste set by the government in Indonesia before being disposed of into the environment. Based on the results of the study, the average COD value of liquid waste produced by PT. XYZ is 97.28 mg / L. This result shows the COD value of liquid waste in PT. XYZ has met the quality standards in accordance with the Regulation of the Minister of Environment Number 5 of 2014 that the maximum limit of COD value in liquid waste is 100 mg / L.